ECMO support as a bridge to lung transplantation is an independent risk factor for bronchial anastomotic dehiscence - Enora Atchade; Mélissa Ren; Sylvain Jean-Baptiste; Alexy Tran Dinh; Sébastien Tanaka; Parvine Tashk; Brice Lortat-Jacob; Maksud Assadi; Gaelle Weisenburger; Hervé Mal; Jean Nicolas Sénémaud; Yves Castier; et al. (BMC Pulmonary Medicine, 2022)
Abstract Background Airway complications are frequent after lung transplantation (LT), as they affect up to 23% of recipients. The implication of perioperative extracorporeal membrane oxygenation (ECMO) support and haemodynamic instability has never been specifically assessed. The first aim of this study was to explore the impact of perioperative ECMO support on bronchial anastomotic dehiscence (BAD) at Day 90 after LT. Methods This prospective observational monocentric study analysed BAD in all consecutive patients who underwent LT in the Bichat Claude Bernard Hospital, Paris, France, between January 2016 and May 2019. BAD visible on bronchial endoscopy and/or tomodensitometry was recorded. A univariate analysis was performed (Fisher’s exacts and Mann–Whitney tests), followed by a multivariate analysis to assess independent risk factors for BAD during the first 90 days after LT (p < 0.05 as significant). The Paris North Hospitals Institutional Review Board approved the study. Results A total of 156 patients were analysed. BAD was observed in the first 90 days in 42 (27%) patients and was the main cause of death in 22 (14%) patients. BAD occurred during the first month after surgery in 34/42 (81%) patients. ECMO support was used as a bridge to LT, during and after surgery in 9 (6%), 117 (75%) and 40 (27%) patients, respectively. On multivariate analysis, ECMO as a bridge to LT (p = 0.04) and septic shock (p = 0.01) were independent risk factors for BAD. Conclusion ECMO as a bridge to LT is an independent risk factor for BAD during the first 90 days after surgery. Close monitoring of bronchial conditions must be performed in these high-risk recipients.